INVESTING IN THE FORAGE BASE IN THE FACE OF CLIMATE CHANGE: ADAPTIVE STRATEGIES FOR LIVESTOCK FARMING (INNOVATIVE ECONOMY, 2025)
Levandivskyi O.T., Svynous I.V., Sas L.S., Shtymak I.V.  INVESTING IN THE FORAGE BASE IN THE FACE OF CLIMATE CHANGE: ADAPTIVE STRATEGIES FOR LIVESTOCK FARMINGPurpose. The aim of the article is a comprehensive study of the investment aspects of the development of the feed base in Ukraine in the context of climate change and the development of adaptive strategies for livestock farming.Methodology of research. In the process of preparing the article, a complex of general scientific and special research methods was used. In particular, a monographic method was used to analyse scientific approaches to investing in the feed base and adapting livestock farming to climate change. System analysis allowed us to identify the relationships between investment decisions, climate risks and the efficiency of feed production. Economic and statistical methods were used to assess the dynamics of investments in the industry and forecast needs taking into account climate scenarios.Findings. It has been established that climate change significantly complicates the functioning of traditional systems of field fodder production, causing a decrease in the yield of fodder crops, degradation of pastures, and instability of the supply of animal feed. This leads to the need to rethink the investment priorities of agricultural enterprises, with an emphasis on adaptive directions for the development of the fodder base. The feasibility of investing in drought-resistant and fast-growing crops, the introduction of resource-saving technologies, local irrigation systems, as well as improving the infrastructure for storage and logistics of feed was substantiated. The potential of digital technologies and bioeconomic planning for increasing the efficiency of managing investments in the feed base was assessed. The results of the study confirm the need to strengthen institutional support from the state and international partners for the formation of sustainable and climate-resilient livestock production systems.Originality. The systematic relationship between climate risks, investment activity of agricultural enterprises and the efficiency of the functioning of the feed infrastructure was substantiated. The significance of the influence of state policy and the institutional environment on the formation of a favourable investment climate in the feed production industry was proved. The conceptual scheme for optimizing investment policy in the field of feed infrastructure development was improved, which involves the implementation of a set of targeted financial instruments taking into account the principles of public and private partnership. This approach allows combining state incentives with private investments to form an effective and sustainable system for providing the livestock industry with feed. Practical value. The results of the conducted research can be used to develop effective investment strategies for the development of the feed base of livestock farming in conditions of climate change. The proposed approaches allow agricultural enterprises to optimize the structure of investments by choosing the most sustainable and economically feasible areas of investment – in particular, in drought-resistant crops, irrigation systems, feed storage infrastructure and digital management technologies. Practical regulations can serve as a basis for risk assessment, increasing the efficiency of agricultural investments and ensuring the stability of production in livestock farms in different regions of Ukraine.Key words: investment, feed base, livestock, climate change, adaptive strategies, agricultural sector, drought-resistant crops, resource conservation, storage infrastructure, digital technologies.
Keywords: investment; feed base; livestock; climate change; adaptive strategies; agricultural sector; drought-resistant crops; resource conservation; storage infrastructure; digital technologies